2017
DOI: 10.3889/oamjms.2017.063
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Level Variations with Different Behavioural Risk Factors in Obese Female Patients

Abstract: AIM:The role of behavioural factors and sleep duration and quality is important in the pathogenesis of obesity. The aim of our study was to evaluate the effects of behavioural risk factors on melatonin secretion in women.SUBJECTS AND METHODS:In total, 120 female patients were enrolled in the study and divided into two groups according to the body mass index. Detailed history, anthropometric measurements, urine and blood samples were evaluated for each patient.RESULTS:Two groups significantly differed in weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The serum level of melatonin in obese subjects seems to have two different phases. In the early stage of obesity, the serum melatonin is elevated, and this elevation is considered as a protective mechanism to fight high free radicals in obesity [ 189 ]. However, in the case of extreme obesity, the melatonin level is significantly reduced compared to the controls [ 190 ].…”
Section: The Outcomes Of Covid-19 Are Potentially Linked To Melatomentioning
confidence: 99%
“…The serum level of melatonin in obese subjects seems to have two different phases. In the early stage of obesity, the serum melatonin is elevated, and this elevation is considered as a protective mechanism to fight high free radicals in obesity [ 189 ]. However, in the case of extreme obesity, the melatonin level is significantly reduced compared to the controls [ 190 ].…”
Section: The Outcomes Of Covid-19 Are Potentially Linked To Melatomentioning
confidence: 99%
“…67 Therefore, at ZT15 (at night) the highest peak of melatonin secretion may have already occurred in females, whereas in males this process is occurring in that point of time. Moreover, hypersecretion during metabolic syndrome, due to an increase of the sympathetic activity in the SCN, 68 could explain the higher levels of this hormone showed by CAF-fed females compared to STD-fed females.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, studies can be found not only concerning the relation between sleep duration and the amount of adipose tissue, but also clarifying the relationship of the mechanism. Too short sleep results in a lower level of leptin and simultaneous growth in ghrelin level [ 8 , 33 , 34 , 35 , 36 ]. Consequently, this may lead to obesity and the development of metabolic disorders [ 9 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep shortening decreases peripheral sensitivity to insulin and promotes hunger. Maintaining a lower activity of insulin and increased intake of calories may result in body weight growth and, consequently, the development of obesity [ 8 , 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%